2021
DOI: 10.14444/8058
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Bone Graft Materials in Spine Fusion: Current Evidence and Future Trends

Abstract: Historically, iliac crest bone autograft has been considered the gold standard bone graft substitute for spinal fusion. However, the significant morbidity associated with harvesting procedures has influenced decision-making and practice patterns. To minimize these side effects, many clinicians have pursued the use of bone graft extenders to minimize the amount of autograft required for fusion in certain applications. Synthetic materials, including a variety of ceramic compounds, are a class that has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Nevertheless, to overcome the limitations of these treatments, especially those related to the lack of availability of patient/donor tissue, synthetic or semi-synthetic materials have been demonstrated to be valid alternatives for the replacement of natural bone stock [ 16 , 17 , 18 , 19 , 20 , 21 ]. Among these, absorbable ceramics such as hydroxyapatite (HA), calcium sulphate, and tricalcium sulphate (TCP), or their combination, are commonly used as bone grafts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to overcome the limitations of these treatments, especially those related to the lack of availability of patient/donor tissue, synthetic or semi-synthetic materials have been demonstrated to be valid alternatives for the replacement of natural bone stock [ 16 , 17 , 18 , 19 , 20 , 21 ]. Among these, absorbable ceramics such as hydroxyapatite (HA), calcium sulphate, and tricalcium sulphate (TCP), or their combination, are commonly used as bone grafts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, the overall trend is consistent with prior literature with a decrease in separate incision autografts in favor of synthetic bone graft materials. 12,13,16 For instance, Lad et al 16 reported a decreasing utilization of iliac crest bone grafts relative to alternatives for all spinal fusion procedures examined from 1993 to 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Iliac crest (separate incision autograft) has long been considered the gold standard grafting material for such procedures. [3][4][5][6] Despite this, local autograft and graft supplements/alternatives have anecdotally been increasingly relied on, 12 presumably to avoid associated complications of separate incision autograft. 5,[7][8][9][10] Numerous studies note the morbidity with harvesting of the iliac crest for autografts and shift focus to the importance of osteogenic materials on spinal fusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous iliac bone graft is the 'gold standard' due to its three desirable properties: osteogenicity, osteoinductivity, and osteoconductivity [ 8 , 9 ]. Nevertheless, graft harvesting can implicate higher morbidity and complications such as chronic pain at the donor site [ 10 12 ]. Different kinds of materials have been developed in order to promote solid fusion at the same time that reduce morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…A new generation of synthetic ceramic bone graft substitutes has gained popularity as they intimately resemble natural bone with intrinsic osteoinductive properties due to their specifically engineered surface microarchitecture, designed to induce cell differentiation and drive bone fusion [ 9 , 10 ]. CBGS is a synthetic bone material composed of tricalcium phosphate (TCP) granules with a polymeric binder able to promote spinal fusions similar to autologous bone graft.…”
Section: Introductionmentioning
confidence: 99%